All Days 1996
DOI: 10.2118/36885-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Drilling Well as Viscometer: Studying the Effects of Well Pressure and Temperature on the Rheology of the Drilling Fluids

Abstract: The current need of drilling ultradeep wells involves facing new technical problems, especially concerning the effects of high pressure and temperature values. When acting along all the vertical profile of the well, the pressure and temperature effects heavily influence the rheology of the drilling fluids. Some of the main drilling parameters which are involved are cutting lifting and hole cleaning efficiencies (resulting both from the variation of the velocity profile of the fluid flow, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Note: The rheological properties of the test fluids together with the associated annulus dimensions and flow rates are used to calculate the corresponding apparent viscosity for each fluid. Formulations presented in (Bourgoyne et al, 1986) and (Maglione et al, 1996) are used to determine this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note: The rheological properties of the test fluids together with the associated annulus dimensions and flow rates are used to calculate the corresponding apparent viscosity for each fluid. Formulations presented in (Bourgoyne et al, 1986) and (Maglione et al, 1996) are used to determine this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Vapp is a calculated test parameter determined using the rheological properties of the test fluids together with the associated annulus dimensions and flow rates. Formulations presented in (Bourgoyne et al, 1986) and (Maglione et al, 1996) are used to determine this parameter. This calculated parameter can be used in determining drilling fluid's flow regime (laminar, transition and turbulent) using the Reynolds number criterion developed for Newtonian fluids (Bourgoyne et al, 1986).…”
Section: Univariate Analysismentioning
confidence: 99%
“…Such a method is available using sophisticated downhole measurement technology that allows us to use the well itself as our measurement tool: a pipe viscometer. Maglione et al (1996) first reported using a well element as a viscometer to study the effect of well pressure and temperature on the rheology of drilling fluids. Since access to the downhole pressure data was not available at the time of the Maglione study, the standpipe pressure was used instead.…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures and pressure may also have large effects on the drilling-fluid density. These effects are thoroughly discussed by Maglione et al (1996), Rommetveit and Bjorkevoll (1997), Herzhaft et al (2001), and Shrivastav (2012).…”
Section: Introductionmentioning
confidence: 99%